2016
DOI: 10.1039/c6ob01878e
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic implications of the enantioselective addition of alkylzinc reagents to aldehydes catalyzed by nickel complexes with α-amino amide ligands

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 126 publications
0
4
0
Order By: Relevance
“…In particular, Me 2 Zn is rather unreactive, and few cases of the addition of Me 2 Zn have been reported. [28] We found that ClCr(Salen) promoted the addition of Me 2 Zn at room temperature, affording excellent results (Scheme 4B). [29] The process was particularly useful in the case of aromatic aldehydes, as the enantiomeric excesses obtained were in the range of 92-99%, with good yields.…”
Section: Salen Ligands In Catalytic Redox Reactionsmentioning
confidence: 87%
“…In particular, Me 2 Zn is rather unreactive, and few cases of the addition of Me 2 Zn have been reported. [28] We found that ClCr(Salen) promoted the addition of Me 2 Zn at room temperature, affording excellent results (Scheme 4B). [29] The process was particularly useful in the case of aromatic aldehydes, as the enantiomeric excesses obtained were in the range of 92-99%, with good yields.…”
Section: Salen Ligands In Catalytic Redox Reactionsmentioning
confidence: 87%
“…Aromatic heterocyclic amines are conventionally challenging to react with alkenes due to their intrinsic nucleophilicity. Within this area, transition metal‐catalyzed hydroamination has enabled the construction of heterocyclic amines, yet harsh conditions are typically required to activate the reaction [33–36] . Nicewicz and co‐workers have made notable advances by designing a photocatalytic system for the intermolecular hydroamination of alkenes, using heterocyclic amines as nitrogen nucleophiles under mild conditions (Figure 1c).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] In addition, α-aminoamides can be used as catalysts and catalytic ligands. [11][12][13] Consequently, various methodologies for the synthesis of α-amino amides have been developed. [14][15][16][17][18][19][20][21][22][23][24][25] The asymmetric synthetic methods have been also researched.…”
Section: Introductionmentioning
confidence: 99%